Audience Motives and Satisfaction on Accessing Online Tours at 360° Virtual Destinasi Indonesia - Endah Murwani; Rismi Juliadi; Agustinus Rusdianto Berto; Rustono Farady Marta (Jurnal Penyuluhan, 2021)
The tourism sector is one of the industries affected by the COVID-19 pandemic. Therefore, the Indonesian Ministry of Tourism and Creative Economy is developing a virtual tour innovation through the "360° Virtual Destinasi Indonesia" program. This research utilizes the Uses and Gratification Theory, which aims to determine the gratification sought and obtained in accessing the "360° Virtual Destinasi Indonesia". Typologies of needs types used are cognitive, affective, personal, and social integration dimensions. This research is explanative research with a survey method. The data were measured by comparing the average Gratification Sought (GS) and Gratification Obtained (GO), and then collected through an online questionnaire to 200 respondents who have accessed the "360° Virtual Destinasi Indonesia" program, using non probability sampling. Data were analyzed using paired t samples test. The results showed that the "360° Virtual Destinasi Indonesia" program fulfills cognitive and personal integration needs. On the other hand, the program does not provide satisfaction on the affective and social integration dimensions. The contribution of this research is it develops the uses and gratification theory in virtual reality and evaluation materials for the Indonesian Ministry of Tourism and Creative Economy.